Analysis of Therapy Satisfaction on the Quality-of-Life of Type 2 Diabetes Mellitus Patients at Anutapura Hospital Palu: Analisis Kepuasan Terapi Terhadap Kualitas Hidup Pasien Diabetes Melitus Tipe 2 di RSUD Anutapura Palu - Zainal, Setiawati Fadhilah; Rumi, Amelia; Tamrin, M.; Rosita, Habiba; Hasymi, Abdurrahman; Alydrus, Rugayyah; Ambianti, Nurul (Universitas Tadulako, 2024)
Background: Type 2 Diabetes Mellitus (Type 2 DM) is a chronic disease characterized by increased blood glucose levels caused by impaired insulin function. In Palu City, Type 2 DM is the 2nd most common in Central Sulawesi with a total of 26,204 people. Objective: This study aims to determine the relationship between therapy satisfaction and the quality of life of Type 2 DM patients who perform outpatient treatment at Anutapura General Hospital, Palu. Methods: With a random sample approach, 100 respondents were used in this cross-sectional study that employed an observational method. Data collection used instruments in the form of a DMSAT (Diabetes Medication Satisfaction Tool) therapy satisfaction questionnaire and a DQOL (Diabetes Quality Of Life) quality of life questionnaire. Results: The results of the study were obtained on therapy satisfaction from Type 2 DM patients with the number of respondents in the very satisfied (1.0%), satisfied (90.0%), and quite satisfied (9.0%) categories while the results of the study of the quality of life of Type 2 DM patients 2 fall into the good category (38.0%), and the bad category (62.0%). The statistical analysis test used was the Spearman Rank Correlation test. The results of the Spearman Rank Correlation test value p = 0.037 or p <Î± (0.05), then H0 is rejected, which means that there is a relationship between satisfaction with therapy and quality of life in patients with Type 2 DM which is very weak. Conclusion: The conclusion in this study is that there is a very weak relationship between therapy satisfaction and quality of life of patients.